Urolithiasis Management in Resource-Limited Settings: A Multicentric Retrospective Study in the Democratic Republic of Congo - DIANGIENDA, PABLO; Moningo, Dieudonné Molamba; Ngoma, Alain; Loposso, Mathieu Nkumu; Daudon, Michel (International Journal of Innovative Research in Medical Science, 2023)
Introduction: Despite the increasing use of minimally invasive surgery techniques in the management of urolithiasis worldwide, resource-limited countries are still experiencing various challenges. This study aims to analyze different therapeutic modalities used in the treatment of urolithiasis in the Democratic Republic of Congo. Methods: After Institutional Review Board approval, records of 194 patients who presented with documented urolithiasis in 13 hospitals across 4 provinces from January 2010 through September 2019 were retrospectively analyzed. The different layers of stones were analyzed by infrared spectrophotometry. Results: Urolithiasis was symptomatic in 52.6% (n=194) of patients. Overall, 86.1% (i.e. 167 out of 194) of stones were removed by surgery, 9.8% spontaneously resolved; 3.1% were extracted after ureteroscopy and 1% of patients had undergone extracorporeal shock wave lithotripsy. Lumbotomy was the most used route (45.2% of cases) in conventional surgery. Conclusion: Most patients in this study were treated by conventional surgery. These results suggest the need to increase the use of minimally invasive surgery.